2015
DOI: 10.1007/s40520-015-0410-8
|View full text |Cite
|
Sign up to set email alerts
|

Problems of older persons using a wheeled walker

Abstract: Problems with opening a door against the direction of walking and the optimization of downhill and uphill walking as well as obstacle crossing should be regarded when developing an intelligent WW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 17 publications
(23 reference statements)
1
46
1
1
Order By: Relevance
“…Speci cally, there was an increased risk of falls when transferring to use the mobility aid and there were safety concerns of not appropriately using the prescribed device. Our assessment tool includes the assessment of transitions between sitting and standing, and the challenges identi ed by Lindemann et al [14] of manoeuvring the walker when navigating doors that open away and towards people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Speci cally, there was an increased risk of falls when transferring to use the mobility aid and there were safety concerns of not appropriately using the prescribed device. Our assessment tool includes the assessment of transitions between sitting and standing, and the challenges identi ed by Lindemann et al [14] of manoeuvring the walker when navigating doors that open away and towards people.…”
Section: Discussionmentioning
confidence: 99%
“…[12,13]. In addition accessibility issues are also a concern, Lindemann et al identi ed opening a door against the direction of walking and obstacle clearance as the biggest problem for older adults using a 4-wheeled walker [14]. In the absence of professional input, the mobility aid may not appropriately compensate for de cits in balance and gait, and the person with dementia not necessarily receive training on safe use of the equipment.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to observe that, during the step in which senior citizens from group 2 were evaluated while holding onto a common walker, the area resulting from the body oscillation was 14.780 cm², raising a question about the frontal body movement required for its use. Different researches have pointed out risks related to the use of common walkers (27) . A study conducted in Holland concluded that the use of common wheel walkers may increase the risk of falling and cause high risk injuries (28) .…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, a walking speed of up to 2 m s −1 (=10 cm/50 ms) or 7.2 km h −1 can be captured. This is in an acceptable range [24][25][26][27][28], especially as the operation of the door reduces the walking speed.…”
Section: Single Doormentioning
confidence: 97%